Changes in steroid metabolism among girls with precocious puberty may not be associated with urinary levels of bisphenol A - Lee, Su Hyeon; Kang, Se Mi; Choi, Man Ho; Lee, Jeongae; Park, Mi Jung; Kim, Shin Hye; Lee, Won-Yong; Hong, Jongki; Chung, Bong Chul (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Precocious puberty (PP) refers to the appearance of physical and hormonal signs of pubertal development at an abnormally early age. Urinary steroid signatures obtained from 42 patients with central PP and 40 patients with peripheral PP were assessed to compare metabolic changes. Levels of androgens such as testosterone, androstenedione, androstenediol, 16 alpha-hydroxy-dehydroepiandrosterone, and 5 alpha-androstenedione tended to be high in both PP groups, and the level of 17 beta-estradiol was higher in the central-PP group (P<0.01) than in the peripheral-PP and 32 age-matched healthy girls. Altered steroid metabolism was also associated with urinary BPA levels, and levels of testosterone, 17 beta-estradiol, and pregnenolone were significantly increased among individuals with high BPA levels. In particular, a correlation was observed between estrogen metabolism and BPA levels irrespective of the type of PP. These findings suggest that in girls, BPA exposure causes metabolic changes in steroidogenesis, but not the early onset of PP. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: 5-ALPHA-REDUCTASE; TESTOSTERONE; ADRENARCHE; EXPOSURE; CHILDREN; PUBARCHE; HORMONE